GERAKAN BEACH CLEAN UP: KAMPANYE KESADARAN LINGKUNGAN DI WILAYAH PESISIR SAMBELIA, LOMBOK TIMUR, NTB - lestariningsih, Wiwid; Himawan, Mahardika Rizqi; Paryono, Paryono; Jefri, Edwin; Nurliah, Nurliah; Rahman, Ibadur; Waspodo, Saptono; Gigentika, Soraya; Damayanti, Ayu Adhita; Larasati, Chandrika Eka; Amir, Sadikin (Jurnal Pepadu, 2024)
The Sambelia coastal area in East Lombok, West Nusa Tenggara (NTB), is rich in marine biodiversity and has great tourism potential. However, the problem of waste, especially plastic waste, poses a serious threat to the sustainability of coastal and marine ecosystems in this region. The Beach Clean Up movement in the Sambelia coastal area aims to tackle the problem of beach waste while increasing environmental awareness among the local community. The methods used for the Beach Clean Up Movement include preliminary studies, activity planning, and coordination with stakeholders. The activity was attended by approximately 200 participants, consisting of 150 students, 10 lecturers, 30 local residents, and 5 tourists. The Beach Clean Up Movement succeeded in reducing the amount of rubbish on the beach, increasing the beauty and comfort of a tourist destination, and supporting the local economy. This activity also effectively increased participants' awareness and knowledge about the dangers of plastic waste and the importance of waste management. The education provided during the activity offered a better understanding of the importance of keeping beaches clean and reducing the use of single-use plastics, which is expected to bring long-term positive changes in waste management behavior.